A Study on the Impact of Robotic Process Automation in Human Resource Management of MSEB with Special Reference to Pune Region (International Journal of Food and Nutritional Sciences, 2025)
Robotic Process Automation (RPA) has emerged as a transformative technology within organizational processes, offering efficiency and accuracy across repetitive tasks. In the context of Human Resource Management (HRM), RPA has the potential to streamline operations, enhance employee productivity, and reshape strategic HR functions. This paper presents a detailed literature review to examine the current body of knowledge concerning the impact of RPA in HRM, with specific reference to its adoption, benefits, challenges, and implications. Focusing on the Maharashtra State Electricity Board (MSEB) in Pune, this paper seeks to identify research gaps and conceptualize a roadmap for future empirical investigation.